Haiku from the Bayou, Back to Bashō, and Beyond: Searching for the Haiku in Translation - MacNeil, Sarah (Université d'Ottawa / University of Ottawa, 2020)
Although the history of the haiku dates back to 8th century Japanese poetic tradition, haiku were not introduced outside of Japan until early 20th century through translation. Since this introduction, original haiku creation outside of the Japanese language has taken off, particularly, in North America, through the works of the Beat poets. Raging parallel to this rise in popularity is the debate around what criteria constitute a haiku once it is removed from its original linguistic and cultural ties. This thesis will explore the difficulties in defining and setting boundaries in haiku translation through a multiple translation approach that allows for both an historic and modern lens on this poetic form. The source-language corpus is pulled from Cajun poet Zachary Richard’s collection Feu. Each selected poem has undergone three translations, to appear through a literal, foreignizing, and mnemonic lens, as a means to explore the nuance and the numerous conceptions of the haiku.
Keywords: Haiku; Translations